Fingerprinting the fungal community - Kennedy, N.; Clipson, N.
Fungi can be found in almost any environment, and play important roles in ecosystem processes such as nutrient cycling and degradation. Despite their importance, the vast majority of fungi have not yet been isolated and identified. Due to the difficulties inherent in culture-based methods, fungal ecologists have turned to community fingerprinting techniques, which utilise signal molecules to profile the fungal members of an environmental sample without culturing. Commonly used signal molecules include chitin, ergosterol, membrane lipids, and nucleic acids.Several DNA-based fingerprinting methods have been successfully applied to fungal communities, including D/TGGE (denaturing/temperature gradient gel electrophoresis), SSCP (single-stranded conformational polymorphism), RISA (ribosomal intergenic spacer analysis), and T-RFLP (terminal restriction length fragment polymorphism). These techniques allow the fungal ecologist to rapidly profile fungal populations in an ecosystem, without the need for laborious culturing or cloning.
Keywords: FUNGAL ECOLOGY; COMMUNITY FINGERPRINTING; DGGE; TGGE; RISA; T-RFLP